Access to oral healthcare services of adolescents of a large-size municipality in northeastern Brazil - Andreza Cristina de Lima Targino Massoni; Érika Porto; Luizy Raquel Barbosa Oliveira Ferreira; Herdesson Pereira Silva; Monalisa da Nóbrega Cesarino Gomes; Matheus França Perazzo; Sérgio D'avila; Ana Flávia Granville-Garcia (Sociedade Brasileira de Pesquisa Odontológica, 2020)
Abstract: The aim of this study was to describe and evaluate access to oral health services among adolescents enrolled in public schools of Campina Grande, Paraíba, Brazil, a large-size municipality in the Northeast of Brazil. An observational, descriptive, analytical, quantitative, and cross-sectional study was carried out through a school survey, in which four validated questionnaires were applied to 438 adolescents aged 12 to 19 years. Data were processed using the SPSS statistical software version 20.0, with bivariate analysis and multivariate analysis through Poisson regression. About 90.9% of adolescents reported having visited the dentist at least once; however, when considering the last 6 months, this percentage fell to 48.4%. Adolescents used private services (50.2%) or the public service (49.8%). About 70.6% of interviewees reported dental treatment (61.1%) as the main reason for seeking the service. Through multivariate analysis, it was observed that the demand for the service was higher among female adolescents (60.5%, p <0.001); the other variables did not present statistically significant differences. In conclusion, the access to oral healthcare services reported by adolescents was good, but there is still a considerable part of this population with no access. Variables that presented significant associated with dental services were gender and toothache history, but only gender remained significant in the multivariate model.